Assessing the Impacts of Emission Reduction Targets on Electricity Pricing and Carbon Mitigation Cost in the BIMSTEC Region - Gyanwali, Khem; Dhungana, Bikash (Journal of Advanced College of Engineering and Management, 2025)
The power sector is a major contributor to global greenhouse gas emissions, making the decarbonization of power grids a critical step toward achieving the commitments outlined in the Paris Agreement. In the BIMSTEC region—comprising India, Bangladesh, Bhutan, Myanmar, Nepal, Thailand, and Sri Lanka—countries face significant challenges due to the uneven distribution of energy resources and rapidly increasing energy demands. This study aims to explore strategies for decarbonizing the power grids of these member states through energy cooperation and the adoption of advanced technologies such as clean hydrogen and carbon capture and storage (CCS). A spatially disaggregated capacity expansion model, utilizing IBM CPLEX Optimization Studio, is developed to minimize total power system costs up to 2050. The model incorporates various policy scenarios to identify optimal pathways. Simulation results indicate that renewable energy sources such as wind, hydro, solar PV, and nuclear will dominate the energy mix, substantially reducing reliance on coal and natural gas under carbon regulation policies. Furthermore, hydrogen storage technology emerges as a crucial solution for addressing resource deficits and maintaining grid stability over both short and long-time horizons. The study also determines appropriate carbon tax rates per tonne of CO2 to support emission reduction targets across different scenarios.